2010
DOI: 10.1007/s00415-010-5488-5
|View full text |Cite
|
Sign up to set email alerts
|

Lateralization of cerebral blood flow in juvenile absence seizures

Abstract: Cerebrovascular blood flow in absence seizures and flow patterns during the ictal period have not been thoroughly investigated. We aimed to evaluate cerebral blood flow changes in typical juvenile absence seizures during the ictal and postictal phases. Seizures were recorded in three patients (mean age: 21 +/- 1 years) with multiple daily typical absence seizures. Simultaneous video electroencephalography and bilateral middle cerebral artery transcranial Doppler ultrasonography recordings were conducted during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…While no studies exist on vascular lateralization there is some support for lateralization of blood flow in seizures, with increases during ictal discharges and decreased blood flow after seizure cessation that was asymmetric between hemispheres. 37 We recently reported similar asymmetric differences in MRI T2 signal and CBF in a preliminary study of FSE patients that underwent MRI evaluations within 6 hrs of SE onset. 38 CBF has been also shown to lateralize with pathology in newborns with focal seizures.…”
Section: Discussionmentioning
confidence: 55%
“…While no studies exist on vascular lateralization there is some support for lateralization of blood flow in seizures, with increases during ictal discharges and decreased blood flow after seizure cessation that was asymmetric between hemispheres. 37 We recently reported similar asymmetric differences in MRI T2 signal and CBF in a preliminary study of FSE patients that underwent MRI evaluations within 6 hrs of SE onset. 38 CBF has been also shown to lateralize with pathology in newborns with focal seizures.…”
Section: Discussionmentioning
confidence: 55%
“…When lateralization was performed FSE pups had a 2% reduction in vessel density (high vs. low) that was significant whilst controls had a 1.6% change that was trending. While no studies exist on vascular lateralization there is some support for lateralization of blood flow in seizures, with increases during ictal discharges and decreased blood flow after seizure cessation that was asymmetric between hemispheres 33 . We recently reported similar asymmetric differences in MRI T2 signal and cerebral blood flow in a preliminary study of FSE patients that underwent MRI evaluations within 6 hrs of SE onset 34 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the global increase, a focal increase in thalamic blood flow of 3.9 to 7.8% following hyperventilation-induced typical absences with GSW discharges was noted 21 . Measurements of CBF using transcranial Doppler ultrasonography in absence seizures 26 and SPECT in IGE 22 and childhood absence epilepsy 23 24 revealed ictal increase and postictal decrease. Conversely, a SPECT study reported that CBF is diffusely reduced throughout the brain during the occurrence of typical absence seizure, whereas CBF increases during the postictal phase 27 .…”
mentioning
confidence: 96%